Energy-efficient, sustainable crop production practices benefit smallholder farmers and the environment across three countries in the Eastern Gangetic Plains, South Asia. (10th February 2020) - Gathala, Mahesh K.; Laing, Alison M.; Tiwari, Thakur P.; Timsina, Jagadish; Islam, Saiful; Bhattacharya, Prateek M.; Dhar, Tapamay; Ghosh, Arunava; Sinha, Abhas K.; Chowdhury, Apurba K.; Hossain, Shakhawat; Hossain, Ilias; et al.
Abstract: In the Eastern Gangetic Plains of South Asia current agronomic practices are energy-intensive, and this contributes to higher cropping system production costs and CO2 -equivalent greenhouse gas emissions. Increasingly uncertain and scarce resources, together with an increasingly variable and changing climate, make conventional crop production vulnerable and unsustainable. We hypothesized that replacing traditional crop management with conservation agriculture based-sustainable intensification practices would reduce energy requirements and CO2 -equivalent emissions while increasing energy use efficiency. Across three major cropping systems (rice-wheat, rice-maize and rice-lentil) we tested improved management practices against a conventional baseline on over 400 on-farm trials. Improved management practices significantly reduced the total energy used in rice-wheat cropping systems, from 30, 045 MJ ha −1 under traditional baseline practice to around 26, 500 MJ ha −1 . Similar savings in total energy used were observed in rice-maize and rice-lentil cropping systems; additionally, energy use was significantly more efficient under improved management in all three cropping systems. CO2 -equivalent emissions were reduced by around 10% under cropping systems with improved management compared to emissions from baseline systems. For all cropping systems the rice-equivalent yield and net income were inversely proportional to the specific energy of the system under improved management but not under traditional practice. This study demonstrated that high cropping system yields under improved management practices increased energy use efficiency while reducing CO2 -equivalent emissions. Our research enables farmers in the Eastern Gangetic Plains to produce more food, more sustainably, under increasing climate variability and change. These results are applicable across the Eastern Gangetic Plains region of over 450 million people and also have broader application for smallholder cropping systems in developing and emerging-economy countries globally. Highlights: Energy usage and CO2 -equivalent emissions were evaluated for different crop management practices in the EGP region of SA. 436 On-farm trials in major cropping systems; rice-wheat, rice-maize, rice-lentil; results are statistically powerful. Improved management practices reduced the total energy usage between 5% and 11% compared to traditional practices. Improved management reduced CO2 -equivalent emissions between 11% and 16% relative to traditional practices.